Studies of removing copper ions from water with the seed coats of grain crops - Stepanova Svetlana; Alekseeva Anna; Suntsova Maria (E3S Web of Conferences, 2023)
This paper presents the studies of sorbing copper ions in simulated water with the seed coats of barley, wheat, and oat grains. Isotherms were built for the Cu2+ sorption at the initial concentrations of 0.315-62.947 mmol/dm3. It is shown that the sorption isotherms of all grain samples correspond with IUPAC 1b and are described by Langmuir equation with the confidence degree of 0.999. It is also shown that sorption runs intensively at the initial contaminant concentration ranging from 0.315 mmol/dm3 through 15.737 mmol/dm3, while the sorption rate observed decreases significantly at the concentration exceeding 15.737 mmol/dm3, which works out to 1,000 mg/dm3. The sorption isotherms built is indicative of monomolecular adsorption running.